PEMANFAATAN LIMBAH CAIR INDUSTRI RUMPUT LAUT SEBAGAI PUPUK ORGANIK CAIR UNTUK TANAMAN PERTANIAN. (Utilization of Liquid Waste from Seaweed Industry as Organic Liquid Fertilizer for Crops) - Justus Elisa Loppies; Medan Yumas (Balai Besar Industri Hasil Perkebunan, 2017)
Utilization of liquid waste from seaweed processing industry to produce organic liquid fertilizer for crops was studied. The liquid waste was taken for both before and after filtration to the waste outlet. Fertilizer was formulated in 60 %, 70 % and 80 % liquid waste and the rest portion as the mixture of banana hump, water hyacinth and seaweed thallus. Fermentation took place unaerobically for 15 days using EM4 microorganisms. Composition of 60 % liquid waste taken before the filtration to the outlet and 40 % of the mixture in the formula showed a fertilizer with the higest auxin, gibberelins cytokinin and ethylen contents of 131.210; 149.550; 183.378 and 18.01 ppm, respectively. In this composition obtained the highest value for phosphate soluble bacteria and Nitrogen fixing bacteria were 7,5 x 104 CFU/ml and 160.000 APM/ml. In fact, in an application test for chili, this formula resulted in the highest growing effects for the crop, in terms of crop height and length, width and number of leaves, compared to other formulas. Moreover, fertilizers formulated from the 70 % and 80 % liquid waste taken before the filtration to the outlet had higher K2O compound, compared to other formulas, while N, Mg, and Ca were found higher in the fertilizer, formulated from the liquid waste taken after the filtration to the outlet.Keywords: liquid waste, seaweed, fertilizer, crops, fermentation, plant growth regulator (PGR). ABSTRAK. Pemanfaatan limbah cair industri pengolahan rumput laut untuk memproduksi pupuk cair organik untuk tanaman pertanian telah diteliti. Limbah cair diambil masing- masing dari sebelum dan sesudah penyaringan ke outlet limbah. Pupuk diformulasi dari 60 %, 70 % dan 80 % limbah cair ditambah sisanya berupa campuran bonggol pisang, enceng gondok, dan thallus hasil sortiran rumput laut. Fermentasi berlangsung secara anaerob selama 15 hari dengan menggunakan mikroorganisme EM4. Komposisi 60 % limbah cair yang diambil sebelum outlet penyaringan dan 40 % campuran bahan- bahan lainnya tersebut, pada formula pupuk menghasilkan kandungan zat pengatur tumbuh auksin, giberelin, sitokinin dan etilen tertinggi dengan kadar masing-masing 131,210; 149,550; 183,378 dan 18,01 ppm. Pada komposisi ini juga diperoleh nilai tertinggi untuk mikroba pelarut fosfat dan mikroba menambat nitrogen adalah 7,5 x 104 CFU/ml dan 160.000 APM/ml. Pada kenyataannya, uji aplikasi formula ini pada tanaman cabe menghasilkan efek pertumbuhan tanaman tertinggi, dalam hal tinggi tanaman dan panjang, lebar dan jumlah daun, dibandingkan dengan formula lainnya. Selanjutnya, pupuk yang diformulasi dari 70 % dan 80 % limbah cair yang diambil sebelum outlet penyaringan memiliki kandungan senyawa K2O lebih tinggi dibanding dengan yang lainnya, sedangkan unsur-unsur N, Mg dan Ca ditemukan pada pupuk yang diformulasi dari limbah cair yang diambil sesudah outlet penyaringan. Kata Kunci: limbah cair, rumput laut, pupuk, tanaman pertanian, fermentasi, zat pengatur tumbuh (ZPT)